2017
DOI: 10.18794/aams/65226
|View full text |Cite
|
Sign up to set email alerts
|

Depth and rate of chest compression in CPR simulation during 10-minute continuous external cardiac compression

Abstract: Depth and rate of chest compression in CPR simulation during 10-minute continuous external cardiac compressionOcena głębokości i częstotliwości kompresji klatki piersiowej podczas symulacji resuscytacji krążeniowo-oddechowej, w trakcie 10-minutowego ciągłego zewnętrznego masażu serca AB ST R ACT I N T R O D U C T I O N:External cardiac massage has been a basic CPR maneuver for years. The aim of the study was to assess the quality of chest compression during a real-time continuous cardiac compression simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…This parameter, as in the case of PL, should be treated as the indicator of the dynamics of the performed maneuver. Our previous study and the suggestions of other authors demonstrated that the rescuer’s body mass is a significant factor allowing deeper CC [26, 32, 33]. Therefore, in our opinion, the analysis of the activity of upper limbs demonstrated that it was impossible to maintain completely straight arms during CC, which is contrary to the other studies.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This parameter, as in the case of PL, should be treated as the indicator of the dynamics of the performed maneuver. Our previous study and the suggestions of other authors demonstrated that the rescuer’s body mass is a significant factor allowing deeper CC [26, 32, 33]. Therefore, in our opinion, the analysis of the activity of upper limbs demonstrated that it was impossible to maintain completely straight arms during CC, which is contrary to the other studies.…”
Section: Discussioncontrasting
confidence: 73%
“…The key question is how to position individual segments to provide the required CC with deflection of 5 cm. The depth of CC is influenced by the rescuer’s body mass, their experience, and the above-mentioned physical fitness and physical condition related to fatigue increasing over time [2628]. Quick rotations of rescuers performing CC that are recommended every 1–2 min may reduce fatigue and improve the quality of CPR [2830].…”
Section: Discussionmentioning
confidence: 99%
“…In the 2020 AHA CPR guidelines, the target chest compression rate is set at 100-120 times per minute [3]. However, the chest compression rate increases as chest compressions are continued [19]. In a previous study, the average compression rate after starting hands-only CPR was found to be 120.97 times/minute in the beginning, increased to 123.69 times/minute after 6 minutes and was 128.06 times/minute after 10 minutes [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them have emphasized on a switching position time for chest compressions, suggesting that rescuers should switch positions every 2 minutes or when fatigue increases [7,8]. However, such measures can be difficult to implement in situations like one-rescuer CPR or during the coronavirus disease 2019 (COVID- 19) pandemic where rescuers have to wear level D protective equipment that minimizes their participation in CPR due to concerns of infection.…”
Section: Introductionmentioning
confidence: 99%
“…This is speculated to be due to increasing fatigue while performing chest compression alone for 8 minutes; however, the frequency of compression was maintained closer to the required frequency of 100 to 120 times/min with the ELCC method. Studying the effects of different frequencies of chest compression on the depth of compression for 8 minutes, Bucki et al 21 reported that all participants became highly fatigued after 2 minutes, at which point the depth of compression dropped to <40 mm. The study also found that greater compression frequencies produced fatigue more quickly, thus causing an early overall slowdown of compressions.…”
Section: Discussionmentioning
confidence: 99%